El marco teórico de los errores y vacíos de la Teoría Monetaria Clásica y Keynesiana sobre el impacto de la expansión monetaria en las tasas de interés y los ciclos económicos (caso peruano 2000-2007) - Rivas Santos, Pablo (2008)
The present article deals about errors vacuum in classical Keynesian theory on the neutrality of money. If classical and Keynesian economists have not been wrong in matters relating to monetary problems, after clinging to his mistakes, could hardly prevail all these disastrous policies, inspired by popular monetary theories, which have disrupted monetary policy in almost all countries.